Periodic solutions for systems of functional-differential semilinear equations at resonance - Amster, Pablo; Epstein, Julián; Sanjuán Cuéllar, Arturo (Topological Methods in Nonlinear Analysis, 2021)
Motivated by Lazer-Leach type results, we study the existence of periodic solutions for systems of functional-differential equations at resonance with an arbitrary even-dimensional kernel and linear deviating terms involving a general delay of the form _0^2πu(t+s)dλ(s), where λ is a finite regular signed measure. Our main technique shall be the Coincidence Degree Theorem due to Mawhin.